Optimization growth performance and intestinal characteristics of broiler through the use of zeolite and bioherbal-based mycotoxin binders as feed additives. - Ibrahim, Ibrahim; Natsir, Muhammad Halim; Sjofjan, Osfar; Djunaidi, Irfan Hadji; Susilo, Agus; Rifa’i, Muhaimin; Hafsah, Hafsah (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This research was designed to explore the potential of mycotoxin binders derived from zeolite and bioherbal formulations as natural feed additives to enhance growth performance and intestinal characteristics in broilers. Materials and Methods: The study utilized 320 Lohmann MB 202 broilers, sourced from PT. Japfa Comfeed Indonesia, commencing from day 1 and extending over a period of 35 days. The methodological framework employed a completely eandomized design, incorporating two factors. The primary factor analyzed was the type of feed additive, designated as Zeolite (A1) and Bioherbal (A2). The secondary factor considered was the level of mycotoxin binder inclusion in the feed, set at four increments: 0% (T1), 0.2% (T2), 0.4% (T3), and 0.6% (T4), resulting in a total of eight treatment combinations, each replicated four times. The observational metrics focused on production performance and specific intestinal characteristics of the broilers. Results: The findings indicated that while the interaction between feed type and the level of additive use did not significantly influence feed consumption, weight gain, feed conversion ratio, or villi length (p > 0.05), there was a notable impact on the villi surface area (p < 0.05) and a pronounced effect on villi count and crypt depth (p < 0.01). Conclusion: The study concluded that mycotoxin binders containing zeolite effectively reduce mycotoxin levels in feed, whereas bioherbal additives significantly improve intestinal health. Thus, a 0.6% inclusion level of these additives is recommended as a viable alternative to antibiotics in broiler chicken diets. J. Adv. Vet. Anim. Res., 12(1): 149–156, March 2025 http://doi.org/10.5455/javar.2025.l882